Magnesium-based hydrogen storage composite material as well as preparation method and application thereof

By adding nickel-zirconium alloy and carbon fibers to the magnesium-based hydrogen storage composite material, and through fine ball milling and extrusion molding processes, the particle size control and stability of magnesium hydride materials in the prior art is solved, achieving efficient storage Hydrogen and multiple cycles are stable.

CN119506741APending Publication Date: 2025-02-25GUODIAN LONGYUAN ENERGY SAVING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411715911.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, it is difficult to accurately control the particle size of magnesium hydride materials by ball milling, and it is easy to introduce impurities. The long ball milling time will lead to material agglomeration and reduce cycle stability.

Method used

Magnesium-based hydrogen storage composite material, containing nanomagnesium hydride, nickel-zirconium alloy and carbon fibers, control the particle size of nanomagnesium hydride to 20-40nm through specific ball milling and extrusion molding processes to ensure efficient hydrogen storage and stability of the material. sex.

Benefits of technology

The rapid hydrogen absorption and discharge rate and multiple cycle stability of magnesium-based hydrogen storage composite materials are achieved, avoiding the agglomeration of materials and the introduction of impurities, and improving the ability to retain hydrogen storage capacity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of hydrogen solid-state storage and utilization, in particular to a magnesium-based hydrogen storage composite material and a preparation method and application thereof. The magnesium-based hydrogen storage composite material contains nano magnesium hydride, a nickel-zirconium alloy and carbon fibers, on the basis of the total weight of the magnesium-based hydrogen storage composite material, the content of the nano magnesium hydride is 84-88 wt%, the content of the nickel-zirconium alloy is 3-5 wt%, and the content of the carbon fiber is 9-11 wt%. In the magnesium-based hydrogen storage material, the particle size of the magnesium hydride nano material is small, so that the diffusion rate of hydrogen in the material is increased, the reaction kinetics of the magnesium hydride nano material can be obviously optimized, the magnesium hydride nano material has high hydrogen absorption and desorption rate, meanwhile, the hydrogen storage capacity of the magnesium-based hydrogen storage material cannot be excessively lost after multiple hydrogen absorption and desorption cycles, and the stability is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solid-state storage and utilization of hydrogen, and in particular to a magnesium-based hydrogen storage composite material and a preparation method and application thereof. Background Art

[0002] As a secondary renewable energy source, hydrogen energy is regarded as the clean energy with the greatest development potential in the 21st century. The high energy density of hydrogen energy is one of its most attractive characteristics, which makes hydrogen energy an excellent fuel and energy carrier. Due to the low density of hydrogen at room temperature and pressure, and its flammable, explosive and easy diffusion characteristics, the storage and transportation of hydrogen have become a bottleneck problem restricting the large-scale application of hydrogen energy. Compared with high-pressure gaseous hydrogen storage and low-temperature liquid hydrogen storage, solid material hydrogen storage can well solve the problems of low hydrogen storage density and poor safety factor of traditional hydrogen storage technology.

[0003] Magnesium-based hydrogen storage materials have the advantages of high hydrogen storage capacity, low price, and abundant magnesium resources in nature. They are considered to be the most promising type of solid hydrogen storage materials. Due to the good stability of MgH2 and the high dehydrogenation enthalpy (75kJ / mol H2), the high dissociation energy of hydrogen molecules on the Mg surface and the slow diffusion rate of hydrogen atoms in the magnesium lattice, the absorption and desorption of hydrogen are thermodynamically stable and kinetically slow, which limits its application in hydrogen storage. At present, the main preparation methods of magnesium hydride nanoparticle materials are: mechanical ball milling, physical / chemical vapor deposition, pyrolysis, electrochemical deposition and plasma. Among them, the ball milling process is relatively simple, but the general high-energy ball mill makes it impossible to accurately control the particle size distribution of the material within a specific range, and it is easy to introduce impurities; when the ball milling time is too long, it is also easy to cause material agglomeration, which reduces the cyclic stability of the material. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems in the prior art that the ball milling method for preparing magnesium hydride materials cannot accurately control the particle size of the material, is easy to introduce impurities, and the long ball milling time will cause material agglomeration and reduce the material cycle stability. A magnesium-based hydrogen storage composite material and a preparation method and application thereof are provided. The material has a faster hydrogen absorption and desorption rate, and at the same time, it will not excessively lose its hydrogen storage capacity after multiple hydrogen absorption and desorption cycles, and has good stability.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a magnesium-based hydrogen storage composite material, which contains nano-magnesium hydride, nickel-zirconium alloy and carbon fiber;

[0006] Based on the total weight of the magnesium-based hydrogen storage composite material, the content of the nano-magnesium hydride is 84-88% by weight, the content of the nickel-zirconium alloy is 3-5% by weight, and the content of the carbon fiber is 9-11% by weight.

[0007] Preferably, the particle size of the nano magnesium hydride is 20-40 nm.

[0008] Preferably, the particle size of the nickel-zirconium alloy is 20-40 nm.

[0009] Preferably, the nickel-zirconium alloy is Zr7Ni 10 Type nickel-zirconium alloy.

[0010] A second aspect of the present invention provides a method for preparing the magnesium-based hydrogen storage composite material as described above, the method comprising the following steps:

[0011] (1) reacting hydrogen and magnesium to obtain magnesium hydride particles;

[0012] (2) ball milling the magnesium hydride particles and nickel-zirconium alloy to obtain nano magnesium hydride;

[0013] (3) Mixing the nano magnesium hydride and carbon fiber obtained in step (2) and extruding them into a mixture.

[0014] Preferably, in step (1), the reaction conditions are: temperature ≥ 350°C, time > 5h, pressure ≥ 10MPa.

[0015] Preferably, the particle size of the magnesium hydride is 90-110 μm.

[0016] Preferably, in step (2), the ball milling process comprises: mixing the magnesium hydride particles and the nickel-zirconium alloy and ball milling them once for 10-15 minutes until the particle size is 1-5 μm, and then ball milling the mixture after the first ball milling for a second time for 5-10 hours until the particle size is 20-40 nm.

[0017] Preferably, in step (2), the ball milling conditions include: a temperature of 5-50° C. and a rotation speed of 300-900 rpm.

[0018] Preferably, in step (2), the ball milling process is carried out under an inert atmosphere.

[0019] Preferably, the inert atmosphere is selected from at least one of nitrogen and an inert gas.

[0020] Preferably, in step (3), the extrusion molding conditions include: pressure ≥ 1 ton / cm 2 .

[0021] A third aspect of the present invention provides an application of the magnesium-based hydrogen storage composite material described above in solid-state hydrogen storage.

[0022] Preferably, the magnesium-based hydrogen storage composite material is used in the form of a hydrogen storage cake, and the hydrogen storage capacity of the hydrogen storage cake is 5.5-7.5%.

[0023] Preferably, the application comprises the following steps: placing the hydrogen storage cake in a hydrogen storage device to perform hydrogenation and / or dehydrogenation reactions.

[0024] Preferably, the conditions for the hydrogenation reaction include: a temperature of 30-180° C. and a hydrogenation time of 6-12 min.

[0025] Preferably, the conditions for the hydrogen release reaction include: a temperature of 175-325° C. and a hydrogen release time of 6-12 min.

[0026] The magnesium-based hydrogen storage composite material of the present invention has a small particle size of the magnesium hydride nanomaterial, which increases the diffusion rate of hydrogen in the material and significantly optimizes the reaction kinetics of the magnesium hydride nanomaterial, thereby accelerating the hydrogen absorption and desorption rate and obtaining good stability.

[0027] The preparation method of the magnesium-based hydrogen storage composite material of the present invention adds nickel-zirconium alloy during the preparation process, and the reaction energy barrier can be effectively reduced through the catalytic effect of the nickel-zirconium alloy; at the same time, the method avoids the introduction of impurities during the preparation of the composite material through high-energy ball milling, and controls the ratio of the added carbon fiber material and the alloy material, as well as the ball milling time to accurately control the particle size of the magnesium hydride nanomaterial to 20-40nm, so that the magnesium-based hydrogen storage composite material with excellent hydrogen absorption and desorption rate and good stability can be stably obtained. DETAILED DESCRIPTION

[0028] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0029] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0030] The magnesium-based hydrogen storage composite material of the present invention contains nano-magnesium hydride, nickel-zirconium alloy and carbon fiber;

[0031] Based on the total weight of the magnesium-based hydrogen storage composite material, the content of the nano-magnesium hydride is 84-88% by weight, the content of the nickel-zirconium alloy is 3-5% by weight, and the content of the carbon fiber is 9-11% by weight.

[0032] In the present invention, the particle size of the nano magnesium hydride can be 20-40nm, and the particle size of the nickel zirconium alloy can be 20-40nm. In the present invention, when the particle sizes of the nano magnesium hydride and the nickel zirconium alloy are within the above range, the hydrogen storage performance of the magnesium-based hydrogen storage composite material is more stable.

[0033] In the present invention, the nickel-zirconium alloy may be Zr7Ni 10 The type of nickel-zirconium alloy, the carbon fiber can be a biomass carbon fiber. In the present invention, when the nickel-zirconium alloy and the carbon fiber are of the above types, the hydrogen storage performance of the magnesium-based hydrogen storage composite material is more stable.

[0034] The magnesium-based hydrogen storage composite material of the present invention can be prepared by combining conventional technical means in the art. In a preferred embodiment, the preparation method of the magnesium-based hydrogen storage composite material includes the following steps:

[0035] (1) reacting hydrogen and magnesium to obtain magnesium hydride particles;

[0036] (2) ball milling the magnesium hydride particles and nickel-zirconium alloy to obtain nano magnesium hydride;

[0037] (3) Mixing the nano magnesium hydride and carbon fiber obtained in step (2) and extruding them into a mixture.

[0038] In the method of the present invention, in step (1), the reaction conditions may be: temperature of 350-600°C, time of 5-10h, and pressure of 10-20MPa. In the method of the present invention, when the reaction conditions are within the above range, the hydrogen storage performance of the prepared magnesium hydride is better.

[0039] In the present invention, in step (1), the reaction can be carried out in a hydrogenation furnace.

[0040] In the present invention, the particle size of the magnesium hydride may be 90-110 μm, preferably 95-105 μm. In the present invention, when the particle size of the magnesium hydride is within the above range (especially within the preferred range), the hydrogen storage performance of the magnesium hydride is better.

[0041] In some embodiments, in step (2), the ball milling process may include: mixing the magnesium hydride particles and the nickel-zirconium alloy and ball milling them once for 10-15 minutes until the particle size is 1-5 μm, and then ball milling the mixture after the first ball milling for a second time for 5-10 hours until the particle size is 20-40 nm. When implemented in the above manner, the hydrogen storage performance of the magnesium hydride is better.

[0042] In the method of the present invention, in step (2), the ball milling conditions may include: a temperature of 5-50°C, preferably 10-40°C; a rotation speed of 300-900rpm, preferably 400-800rpm. In the method of the present invention, when the ball milling conditions are within the above range (especially within the preferred range), the hydrogen storage performance of the magnesium hydride is better.

[0043] In the present invention, in step (2), the ball milling process can be carried out under an inert atmosphere. In a more preferred embodiment, the inert atmosphere is selected from at least one of nitrogen and an inert gas, and more preferably an inert gas.

[0044] In the method of the present invention, in step (3), the extrusion molding conditions may include: a pressure of 1-5 ton / cm 2 , preferably 1.5-3 ton / cm 2 In the method of the present invention, when the extrusion molding conditions are within the above range (especially within the preferred range), the hydrogen storage performance of the prepared magnesium-based hydrogen storage composite material is more stable.

[0045] In some embodiments, the process of preparing the magnesium-based hydrogen storage composite material may include: reacting hydrogen and magnesium in a hydrogenation furnace at 10 MPa or more and 350° C. or more for more than 5 hours to obtain magnesium hydride with a particle size of 90-110 μm; ball-milling the magnesium hydride and nickel-zirconium alloy for 10-15 minutes under an inert atmosphere to a particle size of 1-5 μm at a rotation speed of 300-900 rpm, and then ball-milling the magnesium hydride and the nickel-zirconium alloy for 5-10 hours to a particle size of 20-40 nm at a rotation speed of 300-900 rpm; uniformly mixing the nano-magnesium hydride obtained in the above process with carbon fiber, and heating the mixture under a pressure of 1-5 ton / cm 2 The hydrogen storage cake is extruded into a solid round cake under the conditions of , wherein the content of the nano magnesium hydride is 84-88% by weight, the content of the nickel zirconium alloy is 3-5% by weight, and the content of the carbon fiber is 9-11% by weight. When the preparation method is implemented according to this embodiment, the hydrogen storage performance of the prepared magnesium-based hydrogen storage composite material is more stable.

[0046] The magnesium-based hydrogen storage composite material of the present invention can be used in solid-state hydrogen storage. In a preferred embodiment, the magnesium-based hydrogen storage composite material is used in the form of a hydrogen storage cake, which is a solid disc with a diameter of 30 cm and a thickness of 1 cm, and a hydrogen storage capacity of 5.5-7.5%, preferably 6-7.5%. In the present invention, when the hydrogen storage cake is of the above specifications, the stability, thermal conductivity and oxidation resistance of the hydrogen storage cake are better.

[0047] In some embodiments, the use includes the following steps: placing the hydrogen storage cake in a hydrogen storage device to perform hydrogenation and / or dehydrogenation reactions.

[0048] In the method described in the present invention, the conditions of the hydrogenation reaction may include: temperature of 30-180°C, hydrogenation time of 6-12 min; the conditions of the dehydrogenation reaction may include: temperature of 175-325°C, dehydrogenation time of 6-12 min.

[0049] The magnesium-based hydrogen storage composite material and its preparation method and application described in the present invention are further illustrated by examples. The examples are implemented based on the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.

[0050] The experimental methods in the following examples, unless otherwise specified, are conventional methods in the art.

[0051] Unless otherwise specified, the experimental materials used in the following examples are all commercially available.

[0052] Example 1

[0053] (1) At 10 MPa and 350° C., hydrogen and magnesium are reacted in a hydrogenation furnace for 5 h to produce magnesium hydride particles with a particle size of 94 μm;

[0054] (2) In an argon atmosphere and at a rotation speed of 600 rpm, the magnesium hydride particles and Zr7Ni 10 The nickel-zirconium alloy was mixed and ball-milled for 12 min to a particle size of about 2 μm, and then the mixture after the first ball milling was ball-milled for a second time for 8 h to a particle size of about 21 nm;

[0055] (3) The nano magnesium hydride obtained in step (2) is mixed with carbon fiber and heated to 1 ton / cm 2 The hydrogen storage cake is extruded into a solid round cake under the conditions of , wherein the content of the nano magnesium hydride is 86% by weight, the content of the nickel zirconium alloy is 4% by weight, and the content of the carbon fiber is 10% by weight.

[0056] Example 2

[0057] (1) hydrogen and magnesium were reacted in a hydrogenation furnace at 15 MPa and 400°C for 8 h to obtain magnesium hydride particles with a particle size of 103 μm;

[0058] (2) In an argon atmosphere and at a rotation speed of 300 rpm, the magnesium hydride particles and Zr7Ni 10 The nickel-zirconium alloy was mixed and ball-milled for 15 min to a particle size of about 3 μm, and then the mixture after the first ball milling was ball-milled for a second time for 10 h to a particle size of about 32 nm;

[0059] (3) The nano magnesium hydride obtained in step (2) is mixed evenly with carbon fiber and heated to 2 ton / cm 2 The hydrogen storage cake is extruded into a solid round cake under the conditions of , wherein the content of the nano magnesium hydride is 84 weight %, the content of the nickel zirconium alloy is 5 weight %, and the content of the carbon fiber is 11 weight %.

[0060] Example 3

[0061] (1) reacting hydrogen and magnesium in a hydrogenation furnace at 20 MPa and 450° C. for 10 h to obtain magnesium hydride particles with a particle size of 110 μm;

[0062] (2) In an argon atmosphere and at a rotation speed of 900 rpm, the magnesium hydride particles and Zr7Ni 10 The nickel-zirconium alloy was mixed and ball-milled for 10 min to a particle size of about 5 μm, and then the mixture after the first ball milling was ball-milled for a second time for 5 h to a particle size of about 41 nm;

[0063] (3) The nano magnesium hydride obtained in step (2) was mixed with carbon fiber and heated to 3 ton / cm 2 The hydrogen storage cake is extruded into a solid round cake under the conditions of , wherein the content of the nano magnesium hydride is 88% by weight, the content of the nickel zirconium alloy is 3% by weight, and the content of the carbon fiber is 9% by weight.

[0064] Comparative Example 1

[0065] This comparative example was carried out according to the method of Example 1, except that Zr7Ni was not added in step (2). 10 Type nickel-zirconium alloy.

[0066] (1) At 10 MPa and 350° C., hydrogen and magnesium are reacted in a hydrogenation furnace for 5 h to produce magnesium hydride particles with a particle size of 94 μm;

[0067] (2) in an argon atmosphere at a rotation speed of 600 rpm, the magnesium hydride particles were ball-milled for 12 min until the particle size was about 7 μm, and then the product after the first ball milling was ball-milled for a second time for 8 h until the particle size was about 68 nm;

[0068] (3) The nano magnesium hydride obtained in step (2) is mixed with carbon fiber and heated to 1 ton / cm 2 The hydrogen storage cake is extruded into a solid round cake under the conditions of , wherein the content of the nano magnesium hydride is 86% by weight and the content of the carbon fiber is 14% by weight.

[0069] Comparative Example 2

[0070] In this comparative example, the catalyst is prepared according to the method of Example 1, except that in step (3), the carbon fiber is modified into graphite.

[0071] (1) At 10 MPa and 350° C., hydrogen and magnesium are reacted in a hydrogenation furnace for 5 h to produce magnesium hydride with a particle size of 94 μm;

[0072] (2) In an argon atmosphere and at a rotation speed of 600 rpm, the magnesium hydride particles and Zr7Ni 10 The nickel-zirconium alloy was mixed and ball-milled for 12 minutes to a particle size of about 7 μm, and then the mixture after the first ball milling was ball-milled for a second time for 8 hours to a particle size of about 68 nm;

[0073] (3) The nano magnesium hydride obtained in step (2) is mixed with graphite and heated to 1 ton / cm 2 The hydrogen storage cake is extruded into a solid round cake under the conditions of , wherein the content of the nano magnesium hydride is 86% by weight, the content of the nickel zirconium alloy is 4% by weight, and the content of the graphite is 14% by weight.

[0074] Test Case

[0075] This test example is used to illustrate the hydrogen storage performance and stability of the magnesium-based hydrogen storage composite material of the present invention. The hydrogen storage cakes prepared in Examples 1-3 and Comparative Examples 1 and 2 were placed in a hydrogen storage device to perform hydrogen absorption and desorption experiments at 240-400°C to test their hydrogen storage rate and stability. The results are shown in Table 1.

[0076] Table 1

[0077] Example No. Hydrogen storage rate / % Hydrogen storage rate after 4000 times / % Example 1 7.5 7.1 Example 2 7.3 7.2 Example 3 6.9 6.2 Comparative Example 1 4.1 2.4 Comparative Example 2 4.8 3.5

[0078] It can be seen from the results in Table 1 that the magnesium-based hydrogen storage composite materials prepared in Examples 1-3 by adopting the technical solution of the present invention have excellent hydrogen storage rates, and after 4000 tests, the magnesium-based hydrogen storage composite materials still maintain good hydrogen absorption and desorption performance. However, due to the lack of nickel-zirconium alloy catalyst and carbon fiber in Comparative Example 1 and Comparative Example 2, the hydrogen storage rates and stability of the hydrogen storage materials prepared are inferior to those of the magnesium-based hydrogen storage composite materials prepared in Examples 1-3.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A magnesium-based hydrogen storage composite material, the magnesium-based hydrogen storage composite material comprising nano-magnesium hydride, nickel-zirconium alloy and carbon fiber; Based on the total weight of the magnesium-based hydrogen storage composite material, the content of the nano-magnesium hydride is 84-88% by weight, the content of the nickel-zirconium alloy is 3-5% by weight, and the content of the carbon fiber is 9-11% by weight.

2. The magnesium-based hydrogen storage composite material according to claim 1, characterized in that: The particle size of the nano magnesium hydride is 20-40 nm; and / or The particle size of the nickel-zirconium alloy is 20-40 nm.

3. The magnesium-based hydrogen storage composite material according to claim 1, characterized in that: The nickel-zirconium alloy is Zr7Ni 10 Type nickel-zirconium alloy.

4. A method for preparing the magnesium-based hydrogen storage composite material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) reacting hydrogen and magnesium to obtain magnesium hydride particles; (2) ball milling the magnesium hydride particles and nickel-zirconium alloy to obtain nano magnesium hydride; (3) Mixing the nano magnesium hydride and carbon fiber obtained in step (2) and extruding them into a mixture.

5. The method according to claim 4, characterized in that In step (1), the reaction conditions are: temperature ≥ 350°C, time > 5h, pressure ≥ 10MPa; and / or The particle size of the magnesium hydride is 90-110 μm.

6. The method according to claim 4, characterized in that In step (2), the ball milling process includes: mixing the magnesium hydride particles and the nickel-zirconium alloy and ball milling them for 10-15 minutes to a particle size of 1-5 μm, and then ball milling the mixture after the first ball milling for a second time for 5-10 hours to a particle size of 20-40 nm.

7. The method according to claim 4, characterized in that In step (2), the ball milling conditions include: temperature of 5-50° C. and rotation speed of 300-900 rpm.

8. The method according to claim 4, characterized in that In step (2), the ball milling process is carried out under an inert atmosphere; Preferably, the inert atmosphere is selected from at least one of nitrogen and an inert gas.

9. The method according to claim 4, characterized in that In step (3), the extrusion molding conditions include: pressure ≥ 1 ton / cm 2 .

10. Use of the magnesium-based hydrogen storage composite material according to any one of claims 1 to 3 in solid-state hydrogen storage; Preferably, the magnesium-based hydrogen storage composite material is used in the form of a hydrogen storage cake, and the hydrogen storage capacity of the hydrogen storage cake is 5.5-7.5%.

11. The use according to claim 10, characterized in that: The application comprises the following steps: placing the hydrogen storage cake in a hydrogen storage device to perform hydrogenation and / or dehydrogenation reaction; Preferably, the conditions of the hydrogenation reaction include: temperature of 30-180°C, hydrogenation time of 6-12 min; Preferably, the conditions for the hydrogen release reaction include: a temperature of 175-325° C. and a hydrogen release time of 6-12 min.